2003
DOI: 10.1194/jlr.m200398-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell fatty acid ethyl esters: a significant component of fatty acid ethyl esters in the blood

Abstract: An association between alcoholism and abnormal red blood cell (RBC) size and shape has long been recognized (1). However, the underlying pathophysiologic mechanisms responsible for the morphologic alterations are incompletely understood (2-6). Fatty acid ethyl esters (FAEEs), esterification products of ethanol and fatty acids, have been shown to be incorporated into phospholipid bilayers up to 30 mol % of total membrane fatty acids (7). FAEEs have been implicated as mediators of ethanolinduced organ damage (8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Unlike cholesterol which is evenly distributed between the inner and outer leaflets, the 5 major phospholipids are asymmetrically disposed (outer monolayer: phosphatidylcholine, PC and sphingomyelin, SM; inner monolayer: phosphatidylethanolamine, PE, phosphoinositol, PI and phosphatidylserine, PS) [17,37,38]. In the present study, concentrations of PUFA C18:2, C22:5 and C22:6 were decreased in membrane while concentrations of monounsaturated fatty acid (MUFA) C14:0 and C18:1 were dramatically increased, which resulted in a net higher concentration of total monounsaturated fatty acids in the positive control group [19,39]. Moreover, earlier studies also found that the carbonyls of C18:1 and C16:0 were exposed to the aqueous interface of phospholipids, the C18:1 and C16:0 on membranes may result in increase of rigid molecular order on membrane structures [19,39-42].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Unlike cholesterol which is evenly distributed between the inner and outer leaflets, the 5 major phospholipids are asymmetrically disposed (outer monolayer: phosphatidylcholine, PC and sphingomyelin, SM; inner monolayer: phosphatidylethanolamine, PE, phosphoinositol, PI and phosphatidylserine, PS) [17,37,38]. In the present study, concentrations of PUFA C18:2, C22:5 and C22:6 were decreased in membrane while concentrations of monounsaturated fatty acid (MUFA) C14:0 and C18:1 were dramatically increased, which resulted in a net higher concentration of total monounsaturated fatty acids in the positive control group [19,39]. Moreover, earlier studies also found that the carbonyls of C18:1 and C16:0 were exposed to the aqueous interface of phospholipids, the C18:1 and C16:0 on membranes may result in increase of rigid molecular order on membrane structures [19,39-42].…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, concentrations of PUFA C18:2, C22:5 and C22:6 were decreased in membrane while concentrations of monounsaturated fatty acid (MUFA) C14:0 and C18:1 were dramatically increased, which resulted in a net higher concentration of total monounsaturated fatty acids in the positive control group [19,39]. Moreover, earlier studies also found that the carbonyls of C18:1 and C16:0 were exposed to the aqueous interface of phospholipids, the C18:1 and C16:0 on membranes may result in increase of rigid molecular order on membrane structures [19,39-42]. The worse partition of the fatty acid compositions in the lipid bilayer may alter the biochemical properties of the cell membrane, the membrane shape, organization, and permeability [10,39,41-46].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The cells were washed 3 times with saline and suspended in phosphate buffered saline (pH 7.4), as described in Ref. [27]. The RBCs were then placed between cover slips and imaged without additional preparation.…”
mentioning
confidence: 99%